Fantasy Football and Mathematics : - Flockhart, Dan (Jossey-Bass, 2007)
This workbook is designed to be used in conjunction with Fantasy Basketball and Mathematics: A Resource Guide for Teachers and Parents. The games and activities in Fantasy Basketball and Mathematics were created to get you excited about learning and practicing math, even if you are not a big sports fan. Here's how it works. You will create a Fantasy Basketball team by picking real-life players, following your players' statistics, and calculating your teams' total points using one of the equations your teacher provides. In addition to the basic Fantasy Basketball game, your workbook contains worksheets for extra practice on 46 different math concepts.